2002
DOI: 10.1115/1.1478061
|View full text |Cite
|
Sign up to set email alerts
|

CFD Calculation of a Mixed Flow Pump Characteristic From Shutoff to Maximum Flow

Abstract: The behavior of the flow in a vertical semi-axial mixed flow pump has been analyzed by numerical flow simulations of the entire stage, and the results have been compared to test data. As the flow is expected to be unsteady at part load in such a pump, the steady-state simulations were complemented with unsteady flow simulations of the entire machine at one part load operating point. Pressure measurements at different locations in the casing of the pump provided valuable data for the validation of the calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 4 publications
1
27
0
Order By: Relevance
“…While calculation and test agreed well near BEP, deviations were up to 10 % at partload and high flow. Similar deviations were found in stage calculations published in [60]. When the uncertainties reach ± 10 %, an investigation of the stability of the Q-H-curve becomes questionable.…”
Section: Steady Calculations Of Stages or Complete Pumpssupporting
confidence: 71%
See 2 more Smart Citations
“…While calculation and test agreed well near BEP, deviations were up to 10 % at partload and high flow. Similar deviations were found in stage calculations published in [60]. When the uncertainties reach ± 10 %, an investigation of the stability of the Q-H-curve becomes questionable.…”
Section: Steady Calculations Of Stages or Complete Pumpssupporting
confidence: 71%
“…Ribs in the suction nozzle or the inlet casing must not be omitted. Numerical flow calculations of a semi-axial pump (n q = 155) very well demonstrated the strong impact of ribs at the impeller inlet on the head at low flow, [60].…”
Section: Steady Calculations Of Stages or Complete Pumpsmentioning
confidence: 98%
See 1 more Smart Citation
“…A very satisfactory comparison between calculations and experimental results is presented (see Parrondo-Gayo et al [10]) Several others' works (Gu et al [11]; Muggli et al [12]; Cravero and Marini [13]) have shown good agreement between simulation and experimental results.…”
Section: Cfd In the Turbomachinerymentioning
confidence: 57%
“…Muggli et al [2] reported mixed-flow pump characteristics from shutoff to maximum flow through computational fluid dynamics (CFD) calculations. CFD analysis of the first-stage rotor and stator in a two-stage mixed-flow pump has been performed by Miner [3].…”
Section: Introductionmentioning
confidence: 99%